PROBLEMS OF FORMATION OF SPACE IN THE CREATIVITY OF ARCHITECT HANS SHARUN - Тараненко, Сергій; Бородай, Артем; Бородай, Сергій; Бородай, Яна (SWorldJournal, 2023)
The article describes the role of the architect Hans Scharun in the development of new architectural directions, in particular organic architecture, in the period 1919-1953. Special attention is focused on the artist’s work with forms and space in buildin